Degradable rare earth magnesium alloy bar and preparation method thereof
By introducing specific elements into magnesium alloys and adopting temperature-controlled extrusion technology, Mg-Zn-Mn-Ca-Nd biodegradable magnesium alloy rods are prepared, which solves the inverted relationship between mechanical properties and corrosion resistance of traditional magnesium alloy materials, and achieves high strength, good corrosion resistance and controllable degradation characteristics, which are suitable for bone implantation devices.
Patent Information
- Application Number
- CN202510351916.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-05-02
AI Technical Summary
There is an inverted relationship between mechanical properties and corrosion resistance in traditional magnesium alloy materials, which is difficult to meet the load-bearing and degradation needs of bone implant devices at the same time.
By introducing elements such as Zn, Ca, Mn and Nd into the magnesium alloy, and using 350-410℃ temperature controlled extrusion technology, a coupling control mechanism between dynamic recrystallization and second phase precipitation was established to prepare Mg-Zn-Mn-Ca-Nd biodegradable magnesium alloy rod material.
It realizes the high strength, good corrosion resistance and controllable degradation characteristics of magnesium alloys, and is suitable for bone implantation devices, reducing the need for secondary surgical removal.
Smart Images

Figure HDA0005326263580000011 
Figure HDA0005326263580000012 
Figure HDA0005326263580000021
Abstract
Description
Technical Field
[0001] The invention relates to a biomedical metal material, in particular to a Mg-Zn-Mn-Ca-Nd biodegradable magnesium alloy and a preparation method thereof. Background Art
[0002] At present, the orthopedic implant materials used in clinical applications mainly use non-degradable metals (such as titanium alloys) or degradable polymer materials (such as polylactic acid). Taking bone nails as an example, although titanium alloy materials have excellent mechanical properties, their elastic modulus is significantly higher than that of human cortical bone, which can easily cause stress shielding effects, leading to bone resorption and the risk of secondary fractures; while polylactic acid materials have problems such as insufficient mechanical strength and degradation products causing local acidic environments. Both materials require secondary surgery to remove after implantation.
[0003] In response to the above problems, biodegradable magnesium alloy materials have shown unique advantages. Its elastic modulus (45GPa) is highly matched with human bone tissue (10-30GPa), which can effectively avoid stress shielding, and the degradation products are weakly alkaline, which is conducive to bone healing. However, traditional magnesium alloys have two key bottlenecks: on the one hand, the grains of cast magnesium alloys are coarse (usually >100μm), and the tensile strength is less than 200MPa, which is difficult to meet the needs of fixation of load-bearing parts; on the other hand, the uncontrolled degradation rate in the body (>0.5mm / y) can easily lead to premature mechanical failure. Existing research often loses sight of one thing while focusing on another through single process regulation, and it is difficult to achieve a synergistic improvement in mechanical properties and corrosion resistance.
[0004] The strategic introduction of rare earth elements provides a new idea for breaking through this technical bottleneck. At the same time, different from the traditional sheet processing route, this study innovatively develops high-performance magnesium alloy rod preparation technology. Compared with the banded tissue defects that are easily produced during sheet processing, rod extrusion is more conducive to the formation of continuous tissue evolution characteristics. The present invention establishes a coupling regulation mechanism between dynamic recrystallization and second phase precipitation through 350-410℃ temperature-controlled extrusion technology. This technology is easy to process bionic structures such as bone screw threads, with a material utilization rate of >90%, avoiding increased sensitivity to grain boundary corrosion caused by cutting. This technology breaks through the inverted relationship between strength and corrosion resistance of traditional magnesium alloys, and is particularly suitable for the preparation of bone implant devices with complex stress distribution. Summary of the invention
[0005] The first technical problem to be solved by the present invention is to provide a Mg-Zn-Mn-Ca-Nd biodegradable magnesium alloy rod with good comprehensive mechanical properties, low degradation rate in the human body and no harm to the human body.
[0006] The second technical problem to be solved by the present invention is to provide a method for preparing a Mg-Zn-Mn-Ca-Nd biodegradable magnesium alloy rod, which has the characteristics of simple process and low cost.
[0007] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: to provide a magnesium alloy rod with good mechanical and corrosion resistance properties, wherein the magnesium alloy is a Mg-Zn-Mn-Ca-Nd system; wherein the Zn content is 3.5-4.5wt.%, the Mn content is 0.1-0.3wt.%, the Ca content is 0.1-0.3wt.%, and the Nd content is 0.25-0.75wt.%; the weight ratio of Zn element to Nd element is 5.3-16.0, and the balance is Mg and inevitable impurities.
[0008] The present invention adds human nutritional elements Zn, Ca, Mn and rare earth Nd elements with good biocompatibility. Zn is one of the common alloying elements in magnesium alloys. Zn has a high solid solubility in magnesium and can effectively improve the strength and hardness of the alloy without causing side effects on the human body. Ca is necessary for bone tissue formation, and Mg is 2+ and Ca 2+ When released together, it will be beneficial to the healing of bone tissue. Mn has almost no toxic effect. Adding Mn can eliminate impurities in magnesium alloys and significantly refine the grains. Nd is one of the light rare earth elements. Its cost is lower than that of heavy rare earth elements, and its solid solubility in Mg is lower. Most of it exists in the form of Mg-Zn-Nd second phase in this alloy. The addition of Nd has the effects of grain refinement and second phase strengthening. Rare earth elements increase the dynamic recrystallization temperature of magnesium alloys, allowing large deformation extrusion in the range of 300-400°C, avoiding the problem of grain coarsening during high-temperature processing of traditional magnesium alloys. At the same time, rare earth elements can weaken the basal texture, improve anisotropy, and the axial / radial performance deviation of the rod is <1.1, which is adapted to the multi-directional force requirements of bones.
[0009] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing the biodegradable magnesium alloy rod as described above, characterized in that it comprises the following steps:
[0010] Step 1, material preparation: calculate and weigh the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys; remove the oxide scale and inclusions on the surface of the Mg ingots, Zn ingots, and master alloys;
[0011] Step 2, preheating: preheat the Zn ingot and the master alloy raw material weighed in step 1 to 320-400°C; heat the Mg ingot weighed in step 1 to 730°C, and introduce SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100);
[0012] Step 3, smelting: after the Mg ingot in step 2 is melted, add the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy in sequence, and keep the temperature sufficiently until the master alloy is completely melted; remove the scum on the surface of the magnesium alloy melt; after sufficient stirring, cool to 720°C and keep the temperature for 15 minutes; pour the magnesium alloy melt into a steel mold, cool to room temperature in air, and demold to obtain the desired alloy ingot;
[0013] Step 4: homogenization treatment: the magnesium alloy ingot obtained in step 3 is homogenized in a box-type resistance furnace at a temperature of 330-370°C for 10-12 hours; the homogenized alloy is placed in water for cooling, and taken out when the alloy is cooled to room temperature.
[0014] Step 5, extrusion: the alloy obtained in step 4 is turned into a cylindrical billet, preheated in a box-type resistance furnace at a temperature of 350-410°C for 10-20 min, and extruded after preheating at an extrusion ratio of 10:1-16:1 at a speed of 2.4-2.8 mm / s. After cooling to room temperature in air, a Mg-Zn-Mn-Ca-Nd alloy rod is obtained.
[0015] The content of Mg-Zn-Nd phase in the rod obtained in step (5) is 10.05-10.57%.
[0016] Compared with the prior art, the present invention has the following significant advantages:
[0017] First, through the synergistic effect of light rare earth Nd, Zn and Ca, fine grain strengthening (grain size reduced by more than 50%) and corrosion path optimization (degradation rate reduced by 40%) are simultaneously achieved during extrusion deformation, breaking through the bottleneck of strength-corrosion resistance inversion of traditional magnesium alloys;
[0018] Secondly, the rods prepared by the extrusion process have both high strength and controllable degradation characteristics; the extrusion process can break up the coarse second phase and control its size to 1-5μm, which not only reduces the micro-battery corrosion source, but also forms a dislocation pinning strengthening effect. The mechanical strength can reach: yield strength 196-240MPa, tensile strength 256-283MPa, elongation 14.6-20.4%, Vickers hardness 66-73. The average corrosion rate is 0.4130-0.8147mm / y.
[0019] Third, by replacing precious metal elements with low-cost light rare earths, the production cost is greatly reduced compared to alloys containing heavy rare earths, and the process parameter window is wide, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1These are SEM photos of the degradable rare earth magnesium alloy of the present invention: (a) as-cast; (b) 350°C; (c) 370°C; (d) 390°C; (e) 410°C.
[0021] Figure 2 The data are energy spectrum analysis data of the degradable rare earth magnesium alloy: Mg-4Zn-0.2Mn-0.2Ca-0.5Nd of the present invention after being continuously immersed in Hank's simulated body fluid at 37.4°C for 24 hours.
[0022] Figure 3 SEM morphology of the degradable rare earth magnesium alloy after removing corrosion products of the present invention: (a) cast state (b) 350°C (c) 370°C (d) 390°C (e) 410°C. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the drawings and implementation cases in the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] The element mass percentages of the degradable bio-magnesium alloy in this embodiment are: Zn: 4wt.%, Mn: 0.2wt.%, Ca: 0.2wt.%, Nd: 0.5wt.%, and the rest are inevitable impurities such as Mg, Fe, and Si.
[0026] The present invention provides a biodegradable magnesium alloy rod and a preparation process thereof, comprising the following steps:
[0027] Step 1, material preparation: calculate and weigh the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys; remove the oxide scale and inclusions on the surface of the Mg ingots, Zn ingots, and master alloys;
[0028] Step 2, preheating: preheat the Zn ingot and the master alloy raw material weighed in step 1 to 340°C; heat the Mg ingot weighed in step 1 to 730°C, and introduce SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100);
[0029] Step 3, smelting: after the Mg ingot in step 2 is melted, add the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy in sequence, and keep the temperature sufficiently until the master alloy is completely melted; remove the scum on the surface of the magnesium alloy melt; after sufficient stirring, cool to 720°C and keep the temperature for 15 minutes; pour the magnesium alloy melt into a steel mold, cool to room temperature in air, and demold to obtain the desired alloy ingot;
[0030] Step 4: homogenization treatment: the magnesium alloy ingot obtained in step 3 is homogenized in a box-type resistance furnace at a temperature of 350° C. for 12 h; the homogenized alloy is placed in water for cooling, and taken out when the alloy is cooled to room temperature.
[0031] Step 5, extrusion: the alloy obtained in step 4 is turned into a cylindrical billet, preheated in a box-type resistance furnace at a temperature of 350°C for 20 min, and then extruded at an extrusion ratio of 10:1 and a speed of 2.6 mm / s. After cooling to room temperature in air, a Mg-Zn-Mn-Ca-Nd alloy rod is obtained.
[0032] The grain size of the alloy obtained in this embodiment is greatly reduced compared with the cast state, and the alloy undergoes dynamic recrystallization. The second phase in the alloy is broken and distributed in a band along the extrusion direction, showing a "double peak" structure composed of larger deformed grains and fine grain bands, and the volume fraction of the second phase is 10.33%. The average corrosion rate is 0.4826mm / y, the yield strength is 221MPa, the tensile strength is 275MPa, and the elongation is 14.6%.
[0033] Embodiment 2:
[0034] The element mass percentages of the degradable bio-magnesium alloy in this embodiment are: Zn: 4wt.%, Mn: 0.2wt.%, Ca: 0.2wt.%, Nd: 0.5wt.%, and the rest are inevitable impurities such as Mg, Fe, and Si.
[0035] The present invention provides a biodegradable magnesium alloy and a preparation process thereof, comprising the following steps:
[0036] Step 1, material preparation: calculate and weigh the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys; remove the oxide scale and inclusions on the surface of the Mg ingots, Zn ingots, and master alloys;
[0037] Step 2, preheating: preheat the Zn ingot and the master alloy raw material weighed in step 1 to 340°C; heat the Mg ingot weighed in step 1 to 730°C, and introduce SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100);
[0038] Step 3, smelting: after the Mg ingot in step 2 is melted, add the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy in sequence, and keep the temperature sufficiently until the master alloy is completely melted; remove the scum on the surface of the magnesium alloy melt; after sufficient stirring, cool to 720°C and keep the temperature for 15 minutes; pour the magnesium alloy melt into a steel mold, cool to room temperature in air, and demold to obtain the desired alloy ingot;
[0039] Step 4: homogenization treatment: the magnesium alloy ingot obtained in step 3 is homogenized in a box-type resistance furnace at a temperature of 350° C. for 12 h; the homogenized alloy is placed in water for cooling, and taken out when the alloy is cooled to room temperature.
[0040] Step 5, extrusion: the alloy obtained in step 4 is turned into a cylindrical billet, preheated in a box-type resistance furnace at a temperature of 370°C for 15 min, and then extruded at an extrusion ratio of 10:1 and a speed of 2.6 mm / s. After cooling to room temperature in air, a Mg-Zn-Mn-Ca-Nd alloy rod is obtained.
[0041] The alloy obtained in this example underwent complete dynamic recrystallization, forming a fine and uniform complete recrystallization structure, with a second phase volume fraction of 10.03% and an average grain size of 2.73 μm. The average corrosion rate of the alloy was 0.4130 mm / y, the yield strength was 240 MPa, the tensile strength was 283 MPa, and the elongation was 15.8%.
[0042] Embodiment 3:
[0043] The element mass percentages of the degradable bio-magnesium alloy in this embodiment are: Zn: 4wt.%, Mn: 0.2wt.%, Ca: 0.2wt.%, Nd: 0.5wt.%, and the rest are inevitable impurities such as Mg, Fe, and Si.
[0044] The present invention provides a biodegradable magnesium alloy and a preparation process thereof, comprising the following steps:
[0045] Step 1, material preparation: calculate and weigh the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys; remove the oxide scale and inclusions on the surface of the Mg ingots, Zn ingots, and master alloys;
[0046] Step 2, preheating: preheat the Zn ingot and the master alloy raw material weighed in step 1 to 340°C; heat the Mg ingot weighed in step 1 to 730°C, and introduce SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100);
[0047] Step 3, smelting: after the Mg ingot in step 2 is melted, add the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy in sequence, and keep the temperature sufficiently until the master alloy is completely melted; remove the scum on the surface of the magnesium alloy melt; after sufficient stirring, cool to 720°C and keep the temperature for 15 minutes; pour the magnesium alloy melt into a steel mold, cool to room temperature in air, and demold to obtain the desired alloy ingot;
[0048] Step 4: homogenization treatment: the magnesium alloy ingot obtained in step 3 is homogenized in a box-type resistance furnace at a temperature of 390° C. for 12 h; the homogenized alloy is placed in water for cooling, and taken out when the alloy is cooled to room temperature.
[0049] Step 5, extrusion: the alloy obtained in step 4 is turned into a cylindrical billet, preheated in a box-type resistance furnace at a temperature of 390°C for 12 min, and then extruded at an extrusion ratio of 10:1 and a speed of 2.7 mm / s. After cooling to room temperature in air, a Mg-Zn-Mn-Ca-Nd alloy rod is obtained.
[0050] The alloy grains obtained in this embodiment began to grow, the volume fraction of the second phase was 10.03%, the average grain size was 2.90 μm, the average corrosion rate was 0.6896 mm / y, the yield strength was 204 MPa, the tensile strength was 262 MPa, and the elongation was 18.1%.
[0051] Embodiment 4:
[0052] The element mass percentages of the degradable bio-magnesium alloy in this embodiment are: Zn: 4wt.%, Mn: 0.2wt.%, Ca: 0.2wt.%, Nd: 0.5wt.%, and the rest are inevitable impurities such as Mg, Fe, and Si.
[0053] The present invention provides a biodegradable magnesium alloy and a preparation process thereof, comprising the following steps:
[0054] Step 1, material preparation: calculate and weigh the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys; remove the oxide scale and inclusions on the surface of the Mg ingots, Zn ingots, and master alloys;
[0055] Step 2, preheating: preheat the Zn ingot and the master alloy raw material weighed in step 1 to 340°C; heat the Mg ingot weighed in step 1 to 730°C, and introduce SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100);
[0056] Step 3, smelting: after the Mg ingot in step 2 is melted, add the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy in sequence, and keep the temperature sufficiently until the master alloy is completely melted; remove the scum on the surface of the magnesium alloy melt; after sufficient stirring, cool to 720°C and keep the temperature for 15 minutes; pour the magnesium alloy melt into a steel mold, cool to room temperature in air, and demold to obtain the desired alloy ingot;
[0057] Step 4: homogenization treatment: the magnesium alloy ingot obtained in step 3 is homogenized in a box-type resistance furnace at a temperature of 350° C. for 12 h; the homogenized alloy is placed in water for cooling, and taken out when the alloy is cooled to room temperature.
[0058] Step 5, extrusion: the alloy obtained in step 4 is turned into a cylindrical billet, preheated in a box-type resistance furnace at a temperature of 410°C for 10 min, and then extruded at an extrusion ratio of 10:1 and a speed of 2.7 mm / s. After cooling to room temperature in air, a Mg-Zn-Mn-Ca-Nd alloy rod is obtained.
[0059] The recrystallized grains of the alloy obtained in this embodiment grew significantly, resulting in uneven grain size distribution, with an average grain size of 3.42 μm and a second phase volume fraction of 10.06. The average corrosion rate of the alloy was 0.8147 mm / y, the yield strength was 196 MPa, the tensile strength was 256 MPa, and the elongation was 20.4%.
[0060] Table 1 Comparison of tensile strength, yield strength, elongation and average corrosion rate of Examples 1 to 4
[0061] sample Example 1 Example 2 Example 3 Example 4 Tensile strength / MPa 275 283 262 256 Yield strength / MPa 221 240 204 196 Elongation / % 14.6 15.8 18.1 20.4 <![CDATA[Corrosion rate / mm·y -1 > 0.4862 0.4130 0.6896 0.8147
[0062] Figure 1 The following are SEM photos of the degradable rare earth magnesium alloy of the present invention: (a) as-cast (b) 350°C (c) 370°C (d) 390°C (e) 410°C. It can be seen from the figure that the coarse second phase of the cast alloy is continuously distributed at the grain boundary, and the hot extrusion process breaks the coarse T3 phase into finer granular phases, which are distributed in strips along the extrusion direction. The contact area between the broken phase and the matrix increases, and the number of micro-galvanic couples increases, which theoretically aggravates galvanic corrosion. However, the continuous T3 phase is replaced by discrete particles, cutting off the preferential corrosion channel of the original phase, and the particle size is reduced to reduce the local cathode current density. Although the number of micro-galvanic pairs increases, the dispersed distribution of the broken second phase weakens the galvanic corrosion. The high yield strength of the alloy is mainly attributed to grain refinement, second phase strengthening and dislocation strengthening. Therefore, both mechanical properties and corrosion resistance are improved.
[0063] Figure 2The energy spectrum analysis data of the degradable rare earth magnesium alloy of the present invention: Mg-4Zn-0.2Mn-0.2Ca-0.5Nd after continuous immersion in Hank's simulated body fluid at 37.4°C for 24 hours. From the results, it can be seen that degradation products are generated on the surface of the degradable rare earth magnesium alloy after immersion for 24 hours, mainly hydroxyapatite Ca 10 (PO4)(OH)2 and Mg(OH)2 / MgO passivation films have good biocompatibility. The Ca and P elements detected by energy spectrum are both from Hank's simulated body fluid.
[0064] Figure 3 SEM morphology of the degradable rare earth magnesium alloy after removing corrosion products of the present invention: (a) cast (b) 350℃ (c) 370℃ (d) 390℃ (e) 410℃. The corrosion pits of the cast alloy show a loose layered structure, indicating that the corrosion process has a trend of continuous expansion, and the depth and size of the pits are significantly larger than those of the extruded alloy. In contrast, the surface of the extruded alloy still retains more uncorroded areas, and the overall corrosion damage is low.
[0065] The above-disclosed embodiments are merely features and concepts of the present invention, and are intended to enable professionals and technicians familiar with the relevant fields to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A biodegradable rare earth magnesium alloy rod, characterized in that: The magnesium alloy is a Mg-Zn-Mn-Ca-Nd alloy, and its components are as follows: the content of Zn is 3.5-4.5wt.%, the content of Mn is 0.1-0.3wt.%, the content of Ca is 0.1-0.3wt.%, and Nd is a light rare earth element with a content of 0.25-0.75wt.%. The weight ratio of Zn element to Nd element is 5.3-16.0, and the balance is Mg and unavoidable impurities.
2. The method for preparing a degradable rare earth magnesium alloy rod according to claim 1, characterized in that: The following steps are involved: (1) Weighing the required Mg ingots, Zn ingots, Mg-Mn master alloys, Mg-Ca master alloys, and Mg-Nd master alloys, and removing oxide scales and inclusions on the surfaces of the Mg ingots, Zn ingots, and master alloys; (2) Preheating the weighed Zn ingot and master alloy raw material to a certain temperature, heating the weighed Mg ingot in step 1 to 730° C., and introducing SF6 and N2 protective gases (the volume ratio of SF6 and N2 is 1:100); (3) After the Mg ingot is melted, the preheated Zn ingot, Mg-Nd master alloy, Mg-Ca master alloy, and Mg-Mn master alloy are added in sequence, and the master alloys are kept warm until they are completely melted. The scum on the surface of the magnesium alloy melt is removed, and the temperature is lowered to 720°C and kept warm for 15 minutes after being fully stirred. The magnesium alloy melt is poured into a steel mold, cooled to room temperature in air, and demolded to obtain the desired alloy ingot; (4) homogenizing the alloy ingot at a certain temperature and time, then cooling the alloy in water, and taking it out when the alloy cools to room temperature; (5) The ingot is turned into a cylindrical billet, preheated at a certain temperature and time, and then extruded. The obtained rod is cooled to room temperature in air to obtain a Mg-Zn-Mn-Ca-Nd alloy rod.
3. The preparation method according to claim 2, characterized in that: The preheating temperature in step (2) is 320-400°C.
4. The preparation method according to claim 2, characterized in that: In step (4), the ingot is heat treated and then cooled in water to obtain a billet. The temperature of the homogenization treatment method is 330-370° C. and the time is 10-12 hours.
5. The preparation method according to claim 2, characterized in that: The temperature of the extrusion deformation in step (5) is 350-410° C. and the time is 10-20 min.
6. The preparation method according to claim 2, characterized in that: In step (5), the extrusion ratio is 10:1 to 16:1, and the extrusion speed is 2.4 to 2.8 mm / s.
7. The preparation method according to claim 2, characterized in that: In step (5), quenching is performed by air cooling.
8. The preparation method according to claim 2, characterized in that: The content of Mg-Zn-Nd phase in the rod obtained in step (5) is 10.05-10.57%.
9. The preparation method according to claim 2, characterized in that: The performance range of the rod obtained in step (5) is: yield strength is 196-240MPa, tensile strength is 256-283MPa, elongation is 14.6-20.4%, and average corrosion rate is 0.4130-0.8147mm / y.
10. Use of the degradable rare earth magnesium alloy rod according to claim 1 as a medical orthopedic implant material.